2018
DOI: 10.1111/cpr.12475
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of inflammatory mast cell in fibrosis: Potential therapeutic effect of IL‐37

Abstract: This review summarizes current knowledge on the role of MC in inflammation and tissue/organ fibrosis, with a focus on the therapeutic potential of IL-37-targeting cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 57 publications
(139 reference statements)
1
25
0
Order By: Relevance
“…However, as described above, IL-37 plays an important anti-inflammatory and immunomodulatory capacity in a variety of inflammatory and autoimmune diseases. In addition, IL-37 in vivo could inhibit NLRP3 activation also be mentioned in colitis and LPS-induced disease [19,22,[35][36][37]. In recent study, Rudloff et al reported that IL-37 significantly suppress inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, as described above, IL-37 plays an important anti-inflammatory and immunomodulatory capacity in a variety of inflammatory and autoimmune diseases. In addition, IL-37 in vivo could inhibit NLRP3 activation also be mentioned in colitis and LPS-induced disease [19,22,[35][36][37]. In recent study, Rudloff et al reported that IL-37 significantly suppress inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [38].…”
Section: Discussionsupporting
confidence: 90%
“…Interleukin 37 (IL-37) is a novel cytokine that recently characterized a member in the IL-1 family, which plays a key role in limiting excessive and runaway inflammatory responses via suppressing both innate and adaptive immunity [19][20][21]. It has been demonstrated that a knockdown of endogenous IL-37 in human peripheral blood mononuclear cells, which results in increased production of several pro-inflammatory cytokines [22]. Human IL-37 transgenic mice are protected against metabolic syndrome, systemic inflammation reaction, DSS-induced colitis, and acute myocardial infarction.…”
Section: Irimentioning
confidence: 99%
“…Animal models of chronic skin inflammation highlight potential mast cell roles [127]. Whether in the skin or elsewhere, mast cells influence fibrosis [129,130]. In early scleroderma, there are increased numbers of mast cells in affected skin along with increased circulating plasma histamine [131].…”
Section: The Mast Cell As the Potential Common Denominatormentioning
confidence: 99%
“…The soluble form of ST2 acts as a decoy receptor and captures IL-33 and does not signal; while the cell membrane-linked form has biological activity through the activation of MyD88/NF–κB in several immune cells including MCs. Following the specific binding of IL-33 to the ST2 plasma membrane receptor, NF-κB and MAPK are induced [ 79 ]. IL-33 is secreted by smooth muscle cells, endothelial cells, macrophages, dendritic cells, fibroblasts, epithelial cells, and keratinocytes, all implicated in pSS [ 80 ].…”
Section: Il-33mentioning
confidence: 99%